Review of Creating Equitable Classrooms Through Action Research - Willow Brown (Networks: An Online Journal for Teacher Research, 2009)
For educators frustrated by simplistic prescriptions disconnected from complex classrooms, this book is like a cool drink on a hot day. The editors have assembled ten accounts of teacher research so detailed that readers can smell the chalk dust and picture the faces of students struggling to find belonging and success at school. Each account illustrates teachers’ inquiry and action: problem framing, data collection, reflection, and instructional decisions to increase equity of opportunity and outcomes for all students. Introductory and concluding chapters situate specific initiatives within the contexts of equity pedagogy, which includes two current movements that resonate with teachers: culturally responsive teaching and differentiated instruction. Thus, the book as a whole has inspirational coherence beyond the local initiatives it describes.